FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rintar H.E. Napitupulu (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2012)
The purpose of this research is to analyze empirically the influence of size of audit firm, managerial ownership, audit committee, total assets, profitability, and leverage toward earnings management. The population of the study was listed company in the manufacturing sector at the Indonesia Stock Exchange and the sample was determined based on the following criteria. There were 68 companies meeting the criteria. Data analysis was carried out in terms of financial reports during 2007 until 2010. The samples of this research using purposive sampling and the analysis method used was multiple regressions. The result of this research showed that profitability and leverage had a significant influence on earnings management, while size of audit firm, managerial ownership, and audit committee did not have influence on earnings management.